1994
DOI: 10.1161/01.atv.14.9.1425
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil improves arterial compliance in non-insulin-dependent diabetes mellitus.

Abstract: In a double-blind, placebo-controlled study we investigated the effects of dietary fish oil supplementation on arterial wall characteristics in 20 patients with non-insulin-dependent diabetes mellitus. Estimates reflecting compliance values in the large arteries and more peripheral vasculature, as measured by pulse-contour analysis, improved significantly after 6 weeks of fish oil therapy compared with values recorded at baseline and after 6 weeks' administration of olive oil. The large-artery compliance estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(94 citation statements)
references
References 33 publications
7
81
1
5
Order By: Relevance
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result was consistent with other studies (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002O'Keefe et al, 2006). Large arterial stiffening was associated with hypertension, but both are not identified.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical trials have showed that n-3 fatty acids (fish oil, flaxseed oil or purified eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) supplementation can improve arterial elasticity in normotensive subjects with dyslipidemia, obesity or diabetes (McVeigh et al, 1994;Nestel et al, 1997Nestel et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The trials included in the pooled analyses were small, with a median of 23 patients. Seventeen of the published papers were duplicate publications of six trials [22, 27, 33, 34, 36-38, 40, 42-46, 48, 51, 54, 55]; multiple papers for each trial are indicated by the following grouping of references: [22,38], [27,34,36,37], [40,54,55], [42,48,51], [43,46], [44,45]. There was sufficient information on only 12 of the 98 outcomes to allow data to be pooled, the results of which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic arterial compliance was improved in dyslipidaemic subjects after 7-week supplementation with n-3 eicosapentaenoic acid and docosahexaenoic acid (Nestel et al, 2002). In addition, dietary fish oil supplementation for 6 weeks improved arterial compliance in patients with non-insulin dependent diabetes (McVeigh et al, 1994). Furthermore, n-3 rich flaxseed oil supplementation for 4 weeks increased systemic arterial compliance in obese subjects (Nestel et al, 1997).…”
Section: Discussionmentioning
confidence: 98%